Tendency towards homogenization in fish assemblages in the cascade reservoir system of the Tiete river basin, Brazil - Petesse, Maria Letizia [UNESP]; Petrere, Miguel [UNESP] (Elsevier B.V., 2012)
Measurements of biotic homogenization are important for ascertaining the nature and extent of human impacts on biodiversity, especially in relation to habitat alteration, species introductions and water quality degradation. All of these impacts are typical of impounded systems. Our objectives in this study were to investigate the increasing biotic homogenization and the impacts of introduced species in the Tiete cascade reservoir system (State of São Paulo, Brazil). Biotic homogenization is the replacement of local biota by non-indigeonous species, leading to a gradual increase in biotic similarity over time. In this study, the decades analyzed (1980-89,1990-99 and 2000-2009), revealed the progressive loss of the native species in the system. We used Jaccard's coefficient to measure the changes in biotic homogeneity across decades. In the first comparison (2000s vs. 1980s), the predominant process observed was differentiation, meaning that the biotic assemblages, in the sequence of five reservoirs studied, became more dissimilar. These changes were related to the extirpation of common species from reservoirs. In the second comparison period (2000s vs. 1990s), we observed a tendency towards biotic homogenization, meaning that the number of species in common among reservoirs was increasing. This shift was related to the loss of unique native species and the progressive environmental maturation of each reservoir. The process of homogenization may continue as the reservoirs age and as introduced fish species are dispersed and native species are displaced. For example, we observed the replacement of Geophagus brasiliensis (native) by Geophagus surinamensis (non-native) in the downstream reservoirs, likely due to the introduction of non-native predators (Cichlidae spp.). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biotic homogenization; Fish assemblage; Tiete cascade reservoir system; Brazil